2012
DOI: 10.1071/an11153
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of feet and leg traits of Australian Angus cattle using linear and threshold models

Abstract: The advantages of using a univariate threshold animal model (TAM) over the conventional linear animal model (AM) in the development of a genetic evaluation system for feet and leg traits of Angus cattle were explored. The traits were scored on a scale of 1–9 with scores 5 and 6 being the most desirable. The genetic parameters and estimated breeding values for front feet angle (FA), rear feet angle (RA), front feet claw set (FC), rear feet claw set (RC), rear leg hind view (RH) and rear leg side view (RS) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
2
15
1
Order By: Relevance
“…Previous studies with beef and dairy cattle have demonstrated moderate to high levels of genetic control for feet and leg conformation traits which suggests relevant opportunity for improvement via selection (Häggman et al, 2012;Jeyaruban et al, 2012;Zavadilová and Štípková, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies with beef and dairy cattle have demonstrated moderate to high levels of genetic control for feet and leg conformation traits which suggests relevant opportunity for improvement via selection (Häggman et al, 2012;Jeyaruban et al, 2012;Zavadilová and Štípková, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Strong genetic correlations were found between udder volume and udder attachment, between foot angle and foot depth, between foot angle and leg angle, and between leg angle and foot depth. These genetic correlations were stronger than the ones found in previous studies (Kirschten et al, 2001;Jeyaruban et al 2012). Foot angle and foot depth also showed a strong phenotypic correlation, suggesting that classifiers had difficulties to distinguish between both traits and consequently gave similar scores for the traits.…”
Section: Genetic Correlationscontrasting
confidence: 52%
“…Commercial genomic companies, such as GeneSeek and Zoetis, offer genomic evaluation in Angus. Accuracies range from 0.20 to 0.45 in an Australian validation population (Johnston et al, 2012) and from 0.24 to 0.65 in an American validation population (Northcutt, 2011). In France, genomic evaluations are available for Charolais, Blonde d'Aquitaine, and Limousin.…”
Section: Genomic Selection In the Beef Cattlementioning
confidence: 99%
See 2 more Smart Citations